Resveratrol: a potential medication for the prevention and treatment of varicella zoster virus-induced ischemic stroke - Xu Wang; Hao Chen; Feiyu Song; Kuiyang Zuo; Xin Chen; Xu Zhang; Lanqian Liang; Qiyi Ta; Lin Zhang; Jinhua Li (European Journal of Medical Research, 2023)
Abstract Background Infection rate of varicella zoster virus (VZV) is 95% in humans, and VZV infection is strongly associated with ischemic stroke (IS). However, the underlying molecular mechanisms of VZV-induced IS are still unclear, and there are no effective agents to treat and prevent VZV-induced IS. Objective By integrating bioinformatics, this study explored the interactions between VZV and IS and potential medication to treat and prevent VZV-induced IS. Methods In this study, the VZV and IS datasets from the GEO database were used to specify the common genes. Then, bioinformatics analysis including Gene Ontology, Kyoto Encyclopedia Genes Genomes and Protein–Protein Interaction network analysis was performed. Further, the hub genes, transcription factor (TF) gene interactions, TF-miRNA co-regulatory network and potential drug were obtained. Finally, validation was performed using molecular docking and molecular dynamics simulations. Results The potential molecular mechanisms of VZV-induced IS were studied using multiple bioinformatics tools. Ten hub genes were COL1A2, DCN, PDGFRB, ACTA2, etc. TF genes and miRNAs included JUN, FOS, CREB, BRCA1, PPARG, STAT3, miR-29, etc. A series of mechanism may be involved, such as inflammation, oxidative stress, blood–brain barrier disruption, foam cell generation and among others. Finally, we proposed resveratrol as a potential therapeutic medicine for the prevention and treatment of VZV-induced IS. Molecular docking and molecular dynamics results showed that resveratrol and hub genes exhibited strong binding score. Conclusions Resveratrol could be an alternative for the prevention and treatment of VZV-IS. More in vivo and in vitro studies are needed in the future to fully explore the molecular mechanisms between VZV and IS and for medication development.